Lower temperature (27°C) Decreased Total Motile Sperm Count but not DNA Fragmentation Index in Sperm Preparation with Swim-Up Method in Male Infertility - Jatiningtyas, Abida Zuhra; Indarto, Dono; Qadrijati, Isna; Sari, Yulia; Susanto, Lunardhi; Pangestu, Mulyoto (Bangladesh Journal of Medical Science, 2025)
Background Temperature has a complex impact and is likely to influence the early stages of spermatogenesis. This study aimed to determine the effect of differential temperature in sperm preparation using the swim-up method on total motile sperm count (TMSC) and DNA fragmentation index (DFI) of male infertility. Methods This experimental study recruited 37 infertile male patients who attended the Sekar Fertility Clinic, Dr. Moewardi General Hospital, in November 2020, and we added more participants in December 2022. Before collecting semen samples, all infertile males signed informed consent. The collected sample is divided into 1 ml for sperm preparation in groups A (27°C) and B (37°C). The Wilcoxon test analyzed the data; p <0.05 was considered significant. Results The mean TMSC result in Group A was 17.00 ± 13.06 x106 versus the mean TMSC in Group B at 21.19 ± 17.20 x106; p=0.004, indicating a lower TMSC in Group A. The mean DFI result in group A was 13.74 ± 10.54% versus group B at 13.35 ± 11.78%; p=0.261, also lower in group A. Conclusion Sperm preparation using the swim-up at 27°C significantly lowers TMSC in infertile males compared to 37°C, but the difference in DFI is not significant compared to 37°C. BJMS, Vol. 24 No. 04 October’25 Page : 1222-1227